The Politics of Museums - Gray, Clive. author. aut Link
XI, 186 p. 1 illus.
Keywords: This is the first book to examine how and why museums are political institutions. By concentrating on the ways in which power, ideology and legitimacy work at the international, national and local levels of the museum experience, Clive Gray provides an original analysis of who exercises power and how power is used in museums.